2009
DOI: 10.3164/jcbn.08-250
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxidized Frying Oil on Proteins Related to α-Tocopherol Metabolism in Rat Liver

Abstract: Summary An oxidized frying oil (OFO) diet has been reported to induce an increase in lipid peroxidation and a reduction in vitamin E status in animal tissues. This study was performed to investigate how vitamin E metabolism is influenced by OFO. Male Wistar rats were divided into three groups, a control group (CO) and two OFO-fed groups (OF and OFE). The diet of the OFE group was supplemented with an extra 50 mg/kg of α-tocopherol acetate and thus contained twice as much vitamin E as that of the OF group. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
(65 reference statements)
0
6
0
Order By: Relevance
“…The repeated deep-frying process has been documented to be deleterious to the stability of unsaturated fatty acids and other biochemical parameters such as peroxide content, polar material and acid value [32-34] of dietary cooking oil. Fats are usually oxidized by free radicals at the sites of unsaturated bonds in the fatty acid chains.…”
Section: Discussionmentioning
confidence: 99%
“…The repeated deep-frying process has been documented to be deleterious to the stability of unsaturated fatty acids and other biochemical parameters such as peroxide content, polar material and acid value [32-34] of dietary cooking oil. Fats are usually oxidized by free radicals at the sites of unsaturated bonds in the fatty acid chains.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary OFO-induced oxidative stress and OFO-compromised tissue vitamin E retention have been extensively studied ( 11 – 13 , 34 ) . In the present study, for oral supplementation, we used a level of all- rac -α-tocopherol acetate (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that dietary OFO compromises vitamin E retention in many tissues, and that this can be attributed to a lower vitamin E intake and absorption and a faster catabolism/turnover ( 11 – 13 ) . Due to their relatively low expression of antioxidant enzymes, such as catalase and glutathione peroxidase (GPx), pancreatic β-cells are rather vulnerable to oxidative damage ( 14 , 15 ) .…”
mentioning
confidence: 99%
“…Oxidative stress is an imbalance between oxidation and antioxidation, and is caused by overexposure to oxidants. It has been reported that thermally-oxidized cooking oils promotes lipid peroxidation 7) and causes oxidative damage of various tissues such as liver 8) and pancreas. 9) Oxidized soybean oil intake has been reported to enhance the production of antibodies 10) and inflammatory mediators and to promote lymphocytes proliferation, 11) but little information is available on the relationship between oxidized oil intake and the increased incidence or exacerbation of allergic diseases.…”
Section: Introductionmentioning
confidence: 99%